The Employment Framework in the Preliminary Draft Decree-Law on Civil Property - Santistevan, Jorge (1973)
In 1973, the unveiling of the Social Property Project marked a significant milestone in Peru's social policy landscape, particularly in the realm of business. This initiative brought about notable deviations from the prevailing labor regime. This article endeavors to dissect the newly introduced labor framework outlined in the draft bill and propose enhancements for its refinement. The analysis is structured around three pivotal themes: remuneration, labor rights, and the establishment of trade unions. By juxtaposing the conventional labor regime with the new one, this study aims to delineate the alterations implemented and elucidate the rationale behind these modifications.